Changes in Skeletal Integrity and Marrow Adiposity during High-Fat Diet and after Weight Loss - Scheller, Erica L.; Khoury, Basma; Moller, Kayla L.; Wee, Natalie K. Y.; Khandaker, Shaima; Kozloff, Kenneth M.; Abrishami, Simin H.; Zamarron, Brian F.; Singer, Kanakadurga (Frontiers in Endocrinology, 2016)
The prevalence of obesity has continued to rise over the past three decades leading to significant increases in obesity-related medical care costs from metabolic and non-metabolic sequelae. It is now clear that expansion of body fat leads to an increase in inflammation with systemic effects on metabolism. In mouse models of diet-induced obesity there is also an expansion of bone marrow adipocytes. However, the persistence of these changes after weight-loss has not been well described. The objective of this study was to investigate the impact of high-fat diet (HFD) and subsequent weight-loss on skeletal parameters in C57Bl6/J mice. Male mice were given a normal chow diet (ND) or 60% HFD at 6-weeks of age for 12-, 16-, or 20-weeks. A third group of mice was put on HFD for 12-weeks and then on ND for 8-weeks to mimic weight-loss. After these dietary challenges the tibia and femur were removed and analyzed by microCT for bone morphology. Decalcification followed by osmium staining was used to assess bone marrow adiposity and mechanical testing was performed to assess bone strength. After 12-, 16-, or 20-weeks of HFD, mice had significant weight gain relative to controls. Body mass returned to normal after weight-loss. Marrow adipose tissue (MAT) volume in the tibia increased after 16-weeks of HFD and persisted in the 20-week HFD group. Weight loss prevented HFD-induced MAT expansion. Trabecular bone volume fraction, mineral content, and number were decreased after 12-, 16-, or 20-weeks of HFD, relative to ND controls, with only partial recovery after weight-loss. Mechanical testing demonstrated decreased fracture resistance after 20-weeks of HFD. Loss of mechanical integrity did not recover after weight-loss. Our study demonstrates that HFD causes long-term, persistent changes in bone quality, despite prevention of marrow adipose tissue accumulation, as demonstrated through changes in bone morphology and mechanical strength in a mouse model of diet-induced obesity and weight-loss.